MEDICALIZAÇÃO DA VIDA E O ENCOBRIMENTO DA HABITAÇÃO DA ANGÚSTIA, A LUZ DA FENOMENOLOGIA EXISTENCIAL: UMA REVISÃO INTEGRATIVA DE LITERATURA - MEDEIROS, ANNA KARLA SANTIAGO DE (2022)
The medicalization of life is understood as an active movement to make some events and conditions, until then, considered pertinent and proper to human existence, susceptible to diagnosis, treatment and prevention. Therefore, subjective human issues, such as anguish, are reduced to simple physicalmathematical entities, which disregards the enigmatic character of the experience. However, t he present study is a systematic literature review, in order to reflect on the process of medicalization of life in the covering up and substitution of the dwelling of anguish, in view of the negative implications to the mental health of the subjects. To d o so, we sought to describe theoretically the phenomenon of the medicalization of life; to conceptualize and analyze distress in the light of existentialismphenomenology; to reflect on the issue of the pathologization of distress in the context of contemp orary society, and to identify and reflect on the studies that relate the medicalization of life with the use of psychotropic drugs to cover up the anguish. The search was carried out in the SciELO and Lilacs databases, with a total of 14 articles selected , analyzed according to title, author, database, journal, year of publication, type of study, objectives, and results. The selection criteria for the articles were: produced in Brazil, in Portuguese, in the last fifteen years, related to the area of psycho logy, and showing a connection between the medicalization of life, the experience of anguish, and the devaluation of psychological suffering. The results show: concentration of publications in the Lilacs database; prominence of productions in journals from the psychology area; agglomeration of studies published in the last decade, as well as empirical studies pointing to a process of medicalization of life linked to a biologicist health care model, centered on drug prescription, in which subjective and soci al complaints are medicalized, besides the productions discussing the technifying discourse bringing with it a mythical and magical narrative of the power of medicines and medicine. It is concluded that, besides the need for demedicalizing actions and over coming the biomedical model, it is seen the importance of welcoming the anguish as it presents itself, without trying to cover it up and extinguish it with its pathologization.